2012
DOI: 10.1002/anie.201108139
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Synthesis of Pinacol Alkylboronates from Tosylhydrazones

Abstract: Highly efficient: Pinacol alkylboronates were synthesized by the reaction of tosylhydrazones with bis(pinacolato)diboron or pinacolborane under transition‐metal‐free conditions. This reaction represents an expeditious conversion of carbonyl functionality into a boronate group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(57 citation statements)
references
References 82 publications
0
55
0
2
Order By: Relevance
“…CuBr, CuCl, Cu(OAc) 2 , CuO, and CuSO 4 were found to be efficient catalysts for the tandem C-S/C-N reactions, while CuI gave the best result (Table 1, entries 1-7). In view of recent advances in transition-metalfree reactions [4][5][6][7][8][9][10][11][12][13][14][15], we intentionally performed this reaction without any copper salt as catalyst, and we surprisingly found that the desired product was also obtained ( Table 1, entry 8). We then changed K 2 CO 3 to Na 2 CO 3 , but lower yield was encountered (Table 1, entry 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CuBr, CuCl, Cu(OAc) 2 , CuO, and CuSO 4 were found to be efficient catalysts for the tandem C-S/C-N reactions, while CuI gave the best result (Table 1, entries 1-7). In view of recent advances in transition-metalfree reactions [4][5][6][7][8][9][10][11][12][13][14][15], we intentionally performed this reaction without any copper salt as catalyst, and we surprisingly found that the desired product was also obtained ( Table 1, entry 8). We then changed K 2 CO 3 to Na 2 CO 3 , but lower yield was encountered (Table 1, entry 9).…”
Section: Resultsmentioning
confidence: 99%
“…Early in 2001, Beller first reported a transition-metalfree intra-and intermolecular C-N coupling with aryl chlorides with primary and secondary amines as substrates [4]. Thereafter, a great number of C-X coupling reactions have been developed into transition-metal-free reactions [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[7] Half ac entury later, Morken et al reported an important breakthrough for 1,2-alkyl/aryl migration [8] through carbopallada-tion of vinylboronate complexes with different coupling partners. [12] 1,2-Metalate rearrangement to such products has been demonstrated, [13] either with N 2 as the leaving group in the gem-diborylation of carbenoids [14] or with OBpin (Bpin = pinacolborane) as the leaving group in the gem-diborylation of aldehydes and ketones. [11] Among various organoboron compounds, gem-bis-(boryl)alkanes have drawn increasing attention in recent years due to their unique reactivity in both catalytic and noncatalytic processes to access value-added chemicals.…”
mentioning
confidence: 99%
“…[9a] Fort hese reasons,t he metal-free reaction is highly desirable,a nd indeed, significant progress has been made in the past years. [6,[8][9][10] Themetal-free coupling reactions of diazo compounds generated in situ from Ntosylhydrazones under basic reaction conditions (Bamford-Stevens reaction) [7] have appeared in the recent literature. [8] In pioneering studies,B arluenga, Va ldØs,a nd co-workers discovered metal-free reductive cross-coupling of boronic acids, [9a] phenols,and alcohols [9b] with N-tosylhydrazones.The group of Wang also reported ametal-free reaction to convert N-tosylhydrazones into pinacol boronates.…”
mentioning
confidence: 99%